2009
DOI: 10.5194/hess-13-17-2009
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variability of winter precipitation in the European Alps: relations with the North Atlantic Oscillation.

Abstract: Abstract. The European Alps rely on winter precipitation for various needs in terms of hydropower and other water uses. Major European rivers originate from the Alps and depend on winter precipitation and the consequent spring snow melt for their summer base flows. Understanding the fluctuations in winter rainfall in this region is crucially important to the study of changes in hydrologic regime in river basins, as well as to the management of their water resources. Despite the recognized relevance of winter p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 21 publications
1
44
0
3
Order By: Relevance
“…Many studies have reported main components and characteristics of ACPs and their relationships with precipitation on both regional (e.g. Bartolini et al, 2009) and global scale (e.g. Dore, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported main components and characteristics of ACPs and their relationships with precipitation on both regional (e.g. Bartolini et al, 2009) and global scale (e.g. Dore, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Effects of ACPs, particularly the NAO, on variations in European precipitation have been reported by many studies (e.g. Türkeş and Erlat, 2003;Uvo, 2003;Bartolini et al, 2009;Jaagus 2009;Irannezhad et al, 2014d).…”
Section: Effects Of Atmospheric Circulationmentioning
confidence: 89%
“…In particular, reservoirs are important constituents of power production, as they can react to the electricity consumption variations within seconds and thus ensure sufficient energy supply for adequate network stability. Nevertheless, hydropower production depends on local precipitation, snow coverage, and glacier ice melting, and is therefore subject to important interannual fluctuations [Bartolini et al, 2009;Lambrecht and Mayer, 2009].…”
Section: Introductionmentioning
confidence: 99%